Da ontologia à moral: o problema da conversão da liberdade nos escritos de Sartre - Weidmann, Artur Ricardo de Aguiar (2018)
Conversion of freedom is an issue on Sartre's writings since his first approaches to phenomenological psychology. It has also been on his ontology and, later, on Cahiers pour une morale (1983), one can properly visualize his moral contexture. So, the main concern is to disenthrall the argumentation related to results and moral implication of Sartre’s phenomenological ontology and it's compatibility with a description of the moral existence as in the previously mentioned book. Thereafter, phenomenological basis of his theory of conversion of freedom were examined and described. Likewise, fundamental aspects of Sartre's ontology were examined and discussed in order to establish its metaethical elements, approaching negativities and the original disposal of For-itself to inauthenticity. Besides, the problem of intersubjective relationships, of corporeity and the project of being and its moral implications related to turning inauthenticity into authenticity has been reconstructed. It was intended to establish the elements capable of providing what would be the meaning and the possibility of authenticity as intended by Sartre. Based on that, the thesis is that sartrean argumentation regarding moral conversion of freedom is compatible with the fundamental thesis of his ontology and, consequently, with the foundation of moral sense of authentic existence. This research was developed, first, through analisis and systematization of Sartre’s work on phenomenological psychology as well as Being and Nothingness (2005 [1943]), the posthumous Cahiers pour une morale (1983), among others. Thereafter, Sartre's morality and secondary subjects were analyzed based on complementary bibliography. As a result, we can point the prevalence of the autonomy of irreflective plan and the originary disposition of consciousness to inauthenticity in all its forms. Besides, there is a constant theoretical concern in Sartre's writings on the possibility of a reflexive conversion capable of regain consciousness of its condition of fall in inauthenticity and its alienation. Those ethical concerns are finally clear on Cahiers pour une morale (1983). So that we can conclude that the sense of ethical action in Sartre's work presupposes a conversion of freedom. To changes the relations between men and their own fundamental project, with their own contingency, with corporiety, the world and the others. It's the another way of being of freedom, which means authenticity as a sense of moral action in Sartre’s writings.